MATHS
posted by mo. .
PLEASE REARRANGE FOR B THE FOLLOWING
R=S*B SQUARE/2*T FOR B=
*=MULTIPLY
R= S*B sqrt(2T)
divide by S*Sqrt(2t)
R/(S*Sqrt(2T) ) = B
Respond to this Question
Similar Questions

radical equation
2^x+20=15+3^x A)1 B)16 C)5 D)25 I chose c but i got it wrong i am having a problem understanding it. Let me rewrite the question in a more standard format. 2* sqrt(x)+20=15 + 3*sqrt(x) where * means multiply, and sqrt means the square … 
Algebra
Solve for s: h=(square root of 3)times s/2 and solve for h V= (pi)r squared h / 3 Solve for s: h=(square root of 3)times s/2 Multiply both sides by 2. 2h = (sqrt 3)*s*2/2 which cancels the 2 on the right. 2h = (sqrt 3)*s Now divide … 
math calculus please help!
l = lim as x approaches 0 of x/(the square root of (1+x)  the square root of (1x) decide whether: l=1 or l=0 or l=1 Let me make sure I understand the question. Do we have lim x>0 x/[sqrt(1+x)  sqrt(1x)] ? 
Math(Roots)
sqrt(24) *I don't really get this stuff.Can somebody please help me? 
math,algebra,help
Directions are simplify by combining like terms. x radiacal 18 3 radical 8x^2 can someone show me how to do these types of problems. thanks I cant determine the second term. For the first, I think you meant x sqrt(18) which reduces … 
Math
How do you find a square root of a number that's not a perfect square? 
Mathematics
sqrt 6 * sqrt 8 also sqrt 7 * sqrt 5 6.92820323 and 5.916079783 So you can see the steps — sqrt 6 * sqrt 8 = sqrt 48 sqrt 7 * sqrt 5 = sqrt 35 I hope this helps a little more. Thanks for asking. 
Math Help please!!
Could someone show me how to solve these problems step by step.... I am confused on how to fully break this down to simpliest terms sqrt 3 * sqrt 15= sqrt 6 * sqrt 8 = sqrt 20 * sqrt 5 = since both terms are sqrt , you can combine … 
algebra
simplify: square root of 5 + square root of 20  square root of 27 + square root of 147. simplify: 6/4square root of 2 sqrt 5 + sqrt 20  sqrt 27 + sqrt 147 = sqrt 5 + sqrt (4*5)  sqrt (3*9) + sqrt (49*3) = 3 sqrt 5  3 sqrt 3 + 7 … 
Surds
Solve in the exact form. (sqrt of 4x+1)+(sqrt of x+1)=2 Someone showed me to do this next: Square both sides..so.. 4x+1+2((sqrt of 4x+1)•(sqrt of x+1))=4 I do not understand where the 2 come from ..and why do we need to multiply …